Water extracts of cabbage and kale inhibit ex vivo H2O2-induced DNA damage but not rat hepatocarcinogenesis - M.A. Horst; T.P. Ong; A.A. Jordão Jr.; H. Vannucchi; F.S. Moreno; F.M. Lajolo (Brazilian Journal of Medical and Biological Research, 2010)
The chemopreventive potential of water extracts of the Brassica vegetables cabbage and kale was evaluated by administering their aqueous extracts in drinking water ad libitum to Wistar rats submitted to Ito’s hepatocarcinogenesis model (CB group and K group, respectively - 14 rats per group). Animals submitted to this same model and treated with water were used as controls (W group - 15 rats). Treatment with the vegetable extracts did not inhibit (P > 0.05) placental glutathione S-transferase-positive preneoplastic lesions (PNL). The number of apoptotic bodies did not differ (P > 0.05) among the experimental groups. Ex vivo hydrogen peroxide treatment of rat livers resulted in lower (P < 0.05) DNA strand breakage in cabbage- (107.6 ± 7.8 µm) and kale- (110.8 ± 10.0 µm) treated animals compared with control (120.9 ± 12.7 µm), as evaluated by the single cell gel (comet) assay. Treatment with cabbage (2 ± 0.3 µg/g) or kale (4 ± 0.2 µg/g) resulted in increased (P < 0.05) hepatic lutein concentration compared with control (0.5 ± 0.07 µg/g). Despite the absence of inhibitory effects of cabbage and kale aqueous extracts on PNL, these Brassica vegetables presented protection against DNA damage, an effect possibly related to increased hepatic lutein concentrations. However, it must be pointed out that the cause-effect relationship between lutein levels and protection is hypothetical and remains to be demonstrated.